The Influence of Gusjigang Local Wisdom (Gus) on Developing Students' Sense of Responsibility During School Competitions at SD 1 Barongan - FaiZ, Moh. Najibul; Rondli, Wawan Shokib; Santoso, Denni Agung (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines whether integrating the 'Gus' (good character) value of Gusjigang local wisdom is associated with changes in elementary students' responsibility during school competition activities. A quantitative pre-experimental one-group pretest-posttest design involved all 48 students participating in FLS2N, FTBI, OSN, POPDA, and MAPSI at SD 1 Barongan. Responsibility was measured using a 25-item questionnaire administered before and after the intervention. Instrument validity and reliability were examined, followed by Shapiro-Wilk normality tests and a paired-samples t test. The pretest and posttest data were normally distributed (p = .797 and p = .852). Posttest scores were significantly higher than pretest scores, t(47) = -106.520, p < .001, with a mean paired difference of -21.312. Pretest and posttest scores were also strongly correlated (r = .967, p < .001). Within the limitations of a single-group design, these findings indicate that culturally grounded moral reinforcement through Gusjigang can support responsibility, discipline, and sportsmanship during competition preparation. The study contributes an applicable local-wisdom-based framework for character development in elementary schools.